Design of sustainable porous materials based on 3D-structured silica exoskeletons, Diatomite: Chemico-physical and functional properties. (5th May 2018) - Galzerano, B.; Capasso, I.; Verdolotti, L.; Lavorgna, M.; Vollaro, P.; Caputo, D.; Iannace, S.; Liguori, B.
Abstract: 3D-structured silica exoskeletons-diatomite was used as reactive inorganic ingredient, with and without metakaolin to produce sustainable multifunctional diatomite-based geopolymeric foams. Suitable amount of Silicon powder and vegetable surfactant were used as foaming agents, while polysilicate solution was used as reactive crosslinker. The resulting porous materials, characterized by hierarchical porosity ranging from macro to nano-scale, were fabricated at 40 °C for 24 h and characterized by means of chemical and morphological investigations, contact angle, thermal and acoustic properties and fire reaction. The presence of diatomite in the produced foams provides an increase of thermal inertia, and the thermal insulation performance firstly due to the intrinsically low thermal conductivity of diatomite and also because silicon and vegetable surfactant are able to promote the formation of a co-continuous mesoporous structure. Furthermore, the created morphological structure provides a good acoustic absorption coefficient in a wide range of frequency. Finally, due to their hydrophilicity/oleophobicity character, diatomite-based geopolymeric foams could, potentially, be proposed as oil/water separation membranes. Graphical abstract: Unlabelled Image Highlights: Novel diatomite-based foams were designed by using a natural source, diatomite, vegetable surfactant and silicon powder. The materials design lead to an hierarchical porosity from macro (until 500 μm) to nano-scale (under 50 nm). Hierarchical porosity of the diatomite-based highlight co-existence of acoustic and thermal insulation properties. Diatomite has a significant effect on thermal conductivity reduction, around 46% with respect to the pristine foam. The wettability results highlighted that the diatomite-based foams could be potentially used as oil/water membrane too.